Economic Community Empowerment through Strengthening the Capacity of Jeruk Siam Farmers - Kharisma, Aldhy; Fadri, Zainal; Hanafi, Beni Putra; Irwandi, Irwandi (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2024)
Indonesia is an agricultural country, known for its fertile land, some Indonesian people make their living as farmers and use the fertile land to grow crops. One of the agricultural subsectors is horticulture. One of the horticultural crops is oranges which have an important role in adding economic value to society. As a community, of course Nagari Koto Tinggi must read the climate and match the climate with plants that are suitable for planting. , from the Department of Agriculture in management training, it was found that the climate in Nagari Koto Tinggi is very suitable for planting Siam Oranges. Based on initial observations that researchers found, initially the people of Nagari Koto Tinggi used to improve their economy by going abroad, because the people of Koto Tinggi did not have the expertise to manage land for gardening, first they did not know what plants were suitable for planting, because they had various plants were planted but ultimately died. So in a study conducted by the Department of Agriculture, it was said that Nagari Koto Tinggi was a very suitable area for planting Siamese oranges, so the Department of Agriculture provided training on how to manage Siamese oranges, so that to this day the people of Nagari Koto Tinggi have a livelihood in Siamese orange gardening. From here, the people of Nagari Koto Tinggi, who initially went abroad to make ends meet, began to manage Siamese oranges. Almost every community in Nagari Koto Tinggi has a Siamese orange plantation to meet their living needs and to improve their economy.